Progressive biparietal atrophy: an atypical presentation of Alzheimer's disease. Issue 4 (October 1996) - Ross, S J; Graham, N; Stuart-Green, L; Prins, M; Xuereb, J; Patterson, K; Hodges, J R
Abstract : OBJECTIVES: To define the clinical, neuropsychological, and radiological features of bilateral parietal lobe atrophy. METHODS: Four patients underwent a comprehensive longitudinal neuropsychological assessment, as well as MRI and HMPAO-SPECT. RESULTS: The consistent findings in the patients were early visuospatial problems, agraphia of a predominantly peripheral (or apraxic) type, and difficulty with bimanual tasks, all of which outweighted deficits in memory and language until later in the course of the illness. As the disease progressed, impairments in the phonological aspects of language and in auditory-verbal short term memory were often striking, perhaps reflecting spread from the parietal lobe to perisylvian language areas. Three patients went on to develop a global dementia and fulfilled the criteria for a clinical diagnosis of probable Alzheimer's disease; the fourth patient has only recently been identified. Neuroimaging disclosed bilateral parietal lobe atrophy (MRI) and hypoperfusion (SPECT), which was out of proportion to that seen elsewhere in the brain. One patient has died and had pathologically confirmed Alzheimer's disease with particular concentration in both superior parietal lobes. CONCLUSIONS: Bilateral biparietal atrophy is a recognisable clinical syndrome which can be the presenting feature of Alzheimer's disease. Although the label "posterior cortical atrophy" has been applied to such cases, review of the medical literature suggests that this broad rubric actually consists of two main clinical syndromes with features reflecting involvement of the occipitotemporal (ventral) and biparietal (dorsal) cortical areas respectively.